Stimulation of mucin secretion from human bronchial epithelial cells by mast cell chymase - HE Shao-heng; ZHENG Jian (Acta Pharmacologica Sinica, 2016)
AIM: To investigate the effect of chymase on the mucin secretion from human bronchial epithelial cells. METHODS: Primarily-cultured human bronchial epithelial (PCHBE) cells and normal human bronchial epithelial (NHBE) cells were cultured with chymase or other stimulus in a mixture of bronchial epithelial growth medium (BEGM) and Dulbecco's modified Eagle's medium (DMEM), and the quantities of stimulatory mucin release were recorded. MUC5AC mucin was measured with an ELISA and dolichos biflorus agglutinin (DBA) mucin was determined with an enzyme linked DBA assay. RESULTS: A dose-dependent secretion of DBA mucin from PCHBE cells was observed with chymase with a maximum secretion of 98 % above baseline being achieved following 3 h incubation. The action of chymase started from 1 h, peaked at 3 h and dramatically decreased at 20 h following incubation. Chymase was able to also stimulate approximately 38 % increase in MUC5AC mucin release from PCHBE cells, and about 121 % increase in DBA mucin release from NHBE cells. A chymase inhibitor soybean trypsin inhibitor (SBTI) was able to inhibit up to 85 % chymase induced mucin release, indicating that the enzymatic activity was essential for the actions of chymase on bronchial epithelial cells. CONCLUSION: Chymase is a potent stimulus of mucin secretion from human bronchial epithelial cells. It can contribute to mucus hypersecretion process in the patients with chronic obstructive pulmonary disease or asthma.